Ecological Risk Assessment using Satellite Derived NDVI, HFP and Rainfall Erosivity in Nepal - Baniya, Binod; Karki, Jaya Ram (Cognition, 2022)
Understanding vegetation dynamics is becoming increasingly crucial to maintain ecosystem in the Himalaya region. An assessment of the normalized difference vegetation index (NDVI) and human footprint pressure indicates the ecological risk scenario of Nepal. The original NOAA NDVI product available from 1981-2015 were used. Similarly, Human footprint pressure data for 1993 and 2009 were used. The study purpose was to develop ecological risk map based on NDVI dynamics and human pressure to natural resources. The result showed that the intensity of vegetation dynamics was 0.065 yr-1 with large positive and negative intensities observed in 2006 and 1984, respectively. Both of the intensity of vegetation changes and variance of NDVI showed increased ecological fragility in the Tran-Himalayan region. However, negative correlation between NDVI and rainfall erosivity showed reduced soil erosion and ecological risk in the region. The human footprint pressure has increased up to 43 which together with increasing annual population growth trend (1.35 yr-1) has exerted pressure on the natural system and created ecological risk. The results have important implications for a better understanding of the vegetation dynamics in response to ongoing climatic variability and associated ecological risks in Nepal.